2022
DOI: 10.2196/39799
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mobile Phone App–Based Interventions on Quality of Life and Psychological Symptoms Among Adult Cancer Survivors: Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Background Most patients with cancer experience psychological or physical distress, which can adversely affect their quality of life (QOL). Smartphone app interventions are increasingly being used to improve QOL and psychological outcomes in patients with cancer. However, there is insufficient evidence regarding the effect of this type of intervention, with conflicting results in the literature. Objective In this systematic review and meta-analysis, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…A total of 27 RCTs with 4,986 cancer patients were included in our study ( S3 Appendix ). The characteristics of these studies can be found in the original systematic review [ 27 ]. The ratings of the study participants’ motivations were as follows: for overall motivation, 19 studies (70%) were rated as high motivation, five studies (19%) were rated as moderate motivation, and three studies (11%) were rated as low motivation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 27 RCTs with 4,986 cancer patients were included in our study ( S3 Appendix ). The characteristics of these studies can be found in the original systematic review [ 27 ]. The ratings of the study participants’ motivations were as follows: for overall motivation, 19 studies (70%) were rated as high motivation, five studies (19%) were rated as moderate motivation, and three studies (11%) were rated as low motivation.…”
Section: Resultsmentioning
confidence: 99%
“…We applied the rating to RCTs that were included in a recently published systematic review and meta-analysis about the effect of mHealth app interventions on quality of life (QoL) and psychological outcomes in cancer patients [ 27 ]. The control groups in all studies received usual care, including waitlist control, conventional care, or health education delivered without the use of the mHealth app.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of further research, there is a necessity for the exploration of more streamlined and effective methods to enhance consultation services and expand patients' avenues for information acquisition. Following the COVID-19 epidemic, mobile healthcare has assumed a significant role in patient management [29], and one study's findings [30] (QOL) and self-efficacy, while mitigating anxiety, depression, and distress among adult cancer survivors. Consequently, subsequent studies should endeavor to leverage this modality to fulfill the health system and information requisites of prostate cancer survivors.…”
Section: Unmet Supportive Care Needsmentioning
confidence: 99%
“…Health apps provide a complement to in-person care and present an opportunity to ease the strain faced by clinicians and health systems which is partially due to a shortage of healthcare professionals 2,3 . A number of recent studies have demonstrated beneficial effects of health apps on health outcomes and quality of life 4 , including in condition areas such as mental health 5,6 , diabetes [7][8][9] , hypertension 7 , cancer 10,11 , and asthma 12 . Moreover, health apps can contribute to cost savings and to more efficient use of health system resources that are facing an increasing demand 13,14 .…”
Section: Introductionmentioning
confidence: 99%